Primary amino acids affect the distribution of methylmercury rather than inorganic mercury among tissues of two farmed-raised fish species. (June 2019) - Man, Yi; Yin, Runsheng; Cai, Kai; Qin, Chongyang; Wang, Jianxu; Yan, Haiyu; Li, Miling
Abstract: The distributions of primary amino acids, MeHg and IHg in body tissues of two commonly farm-raised fish species (common carp: Cyprinus carpio ; grass carp: Ctenopharyngodon idellus ) in Guizhou Province, SW China, were investigated to understand the effects of primary amino acids on MeHg and IHg metabolism in farm-raised fish. The primary amino acids were classified into four groups: (1) essential and polar amino acids; (2) essential and non-polar amino acids; (3) non-essential and polar amino acids; and (4) non-essential and non-polar amino acids. For both fish species, groups (1, 2 and 3) were enriched in muscle and kidney, whereas group (4) was enriched in scale. The two fish species showed low MeHg concentrations (grass carp: 0.5–3.9 ng/g; common carp:1.0–7.4 ng/g) and low MeHg proportions (grass carp: 2–45%; common carp: 6–37%) in their tissues, which are mainly due to the simple food web structures and the fast growth of the farm-raised fish. Positive correlations ( r = 0.342 to 0.472; p < 0.01; n = 78) were observed between MeHg and several primary amino acids (cysteine, threonine, phenylalanine, leucine, valine, glutamate serine and tyrosine) in fish tissues, which may be driven by the formation of MeHg-Cys complexes within fish body. However, no significant correlations were observed between IHg and any primary amino acids, indicating the metabolic processes of IHg and MeHg are different. This study advances our understanding that cysteine and its related/derived amino acids may be an important driving force for MeHg distribution and translocation in fish. Graphical abstract: Image 107220 Highlights: Methylmercury is rich in protein-rich fish tissues. Cysteine and its related/derived amino acids have a high biological association with methylmercury. The formation of MeHg-Cys complexes can be an important driving force for methylmercury distribution in fish bodies. Abstract : Capsule: Cysteine and its related/derived amino acids may be an important driving force for MeHg distribution and translocation in fish.